The Effect of Telephone-Administered Cognitive-Behavioral Therapy on Quality of Life among Patients with Multiple Sclerosis - Cosio, David (2011)
BACKGROUND: Past research has found that a variety of physical, psychological, and social factors can affect quality of life (QOL). These previous findings suggest that interventions that address these factors could potentially improve QOL. PURPOSE: The purpose of this study was to examine whether cognitive behavioral therapy (CBT) can improve QOL, and if so, explore which factors might mediate this effect. METHODS: This is a secondary analysis of a randomized controlled trial. One hundred twenty seven participants with multiple sclerosis (MS) and depression were randomly assigned to either a telephone-administered CBT (T-CBT) or telephone-administered supportive emotion focused therapy (T-SEFT) intervention. RESULTS: Patients assigned to T-CBT showed significantly greater improvements in QOL compared to those assigned to T-SEFT. The greater improvement in QOL among T-CBT recipients was mediated by improvements in depression and positive affect. There was also inconsistent support for the superior effect of CBT on QOL being mediated by improvement in fatigue. CONCLUSIONS: T-CBT provided greater QOL benefits compared to T-SEFT, which controlled for non-specific treatment components. This study further suggests that T-CBT procedures specific to the management of depression and positive affect were uniquely useful in improving QOL.